Disputas em torno da Ritalina: uma análise sobre diferentes possibilidades de um fármaco - Maia, Igor Fidelis (2017)
This dissertation presents a historical and sociological research about Ritalin's ability to produce social normalization. Therefore, an analysis was made of the trajectory of this drug, of speeches publicly pronounced by its users and a self-reflection anchored in the objective effects of Ritalin on the researcher's body. There is a comparison between the widely-used speech that this drug produces obedience to social norms, and the empirical material that I had contact throughout the research. This psychotropic drug is one of the most consumed in the world, and also one that brings together the most criticism and controversy. Popularly called as the pill of obedience, is directly associated with medicalization of children at school and has been accused of being able to produce a genocide of the future. Two uses of this drugs are distinguished here: the people who have the diagnosis of Attention Deficit/Hyperactivity Disorder (ADHD), and those who use ritalin as a cognitive enhancer which maximizes the concentration in study activities. From an investigation based on the history of this drug, in the declarations of its users on two electronic addresses, and in the researcher's experience, a network of heterogeneous relations involving the consumption of Ritalin was evidenced, even though insistently have been characterized as normalized or obedient.